1983
DOI: 10.1007/bf00046906
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in cancer metastases and their relevance to metastatic growth

Abstract: The dissemination of malignant cells throughout the body to form secondary growths is a highly complex process dependent upon both host and tumor cell properties. One potential defensive system which could influence the outcome of metastasis is the mononuclear phagocyte system. Although macrophages have been observed in essentially all primary and metastatic tumors examined regardless of histologic type or anatomic location, the biological significance of these observations is far from clear. What is clear, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Tumors are generally associated with hypoxia and the infiltration of inflammatory cells (22,23). Thus, it is reasonable to hypothesize that this negative feedback system might not operate efficiently in tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors are generally associated with hypoxia and the infiltration of inflammatory cells (22,23). Thus, it is reasonable to hypothesize that this negative feedback system might not operate efficiently in tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding hypoxia, we analyzed about 5 kb upstream of the 5′ flanking region of the vasohibin gene, but we did not find any consensus sequences of hypoxiaresponsive elements. Nevertheless, it is well known that tumors are associated with hypoxia as well as the infiltration of inflammatory cells (22,23). Therefore, this negative feedback system may not operate efficiently in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages have shown to actively invade solid tumors [15,18] and have cytotoxic activity against a variety of tumor cells [10,18,19,28,33]. Macrophages also have been implicated variously in potentiating [9,13] or inhibiting metastatic potential [10,11,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Amarillo, TX 79106, USA Studies in other tumor systems have shown that macrophages are necessary for the stimulation of antitumor immunity [33], and that a normal macrophage population is necessary for adoptive transfer of antitumor immunity by lymphoid cells [34]. Macrophages may contribute to lymphocyte-mediated antitumor immunity by presentation of tumor antigen and elaboration of interleukin-1 (IL-1) [22,24], or they may be directly cytotoxic to tumor cells after activation [15,19,25,31]. Macrophages have shown to actively invade solid tumors [15,18] and have cytotoxic activity against a variety of tumor cells [10,18,19,28,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation